Susi Pudjiastuti's Rationality in Financing SKPT: A JICA Grant Program Perspective - Rohman Kholid, Arif Nuru; Rahayu, Dini Septyana (Mediasi Journal of International Relations, 2023)
The exploitation of natural sources in Indonesian waters by foreign-flagged vessels and lacking attention to fishermen communities were two main problems that had to be solved by Susi Pudjiastuti during her service as the Minister of Maritime Affairs and Fisheries of Indonesia. Various policies, such as sinking vessels and distributing the subsidy to the public need, had already been undertaken. However, these types of policies will be potentially revised along with the regime change. The Integrated Center of Marine and Fisheries or Sentra Kelautan dan Perikanan Terpadu (SKPT) built in several outer islands of Indonesia became an alternative solution for maximizing the supervision and development of the national fishery. On the other hand, this project needs a large amount of budget. Therefore, Susi Pudjiastuti selected foreign aid as an alternative option in realizing the idea, which became the research main topic. Through Rational Choice Theory by Stephen Waltz, this research explains that foreign aid for SKPT had been resulted from Susi's decisions as a rational actor. Several potential actors had been chosen as lobbying targets. Based on various considerations and complexity in Susi's interactions with these actors, Japan was finally considered the most prospective entity. Various approaches later were conducted by MMAF to Japan. As a result, Japan through the Japan International Cooperation Agency (JICA) had agreed to assign a grant program to SKPT, and It had been recorded as the foreign aid with the greatest value along the the history of Japan’s aid to Indonesia.